KEUNIKAN KITAB TAFSIR TARJUMAN AL-MUSTAFID KARYA ABDURAUF AS-SINGKILI - Nur Syafiqah Binti Nahlil; Muhith (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Tarjuman al-Mustafid by Abdurauf as-Singkili is widely regarded as an early landmark of Malay Qur’anic exegesis, mediating classical Arabic tafsir heritage for Muslim readers in the Malay Indonesian world. Yet its “distinctiveness” is often stated in broad terms without clear textual indicators. Objective: this study aims to identify and explain the distinctive features of Tarjuman al-Mustafid in language, method, exegetical orientation, and its strategy of transmitting earlier authorities. Method a qualitative library based study employing content analysis on selected textual units (renderings of meaning, brief clarifications, legal hints, and moral ethical emphases), complemented by a historical intellectual reading of the Aceh Malay context. Results the tafsir shows a communicative Malay religious register, a preference for concise exposition that foregrounds the verse’s overall sense, selective notes oriented to piety and practice, and a compact adaptation of widely used classical tafsir sources without extended technical debate. Conclusion: Tarjuman al-Mustafid is distinctive for its pedagogical bridging function, helping to institutionalize a Malay tafsir tradition and shaping later developments of Nusantara exegesis.